Confronting AIDS : public priorities in a global epidemic (OUP New YorkUS, 1999)
Provides information and analysis to help policymakers, development specialists, public health expets, and others who shape the public response to HIV/AIDS to design an effective strategy for confronting the epidemic. Draws upon three bodies of knowledge: the epidemiology of HIV; public helath insights into disease control; and especially public economics which focuses on assessing trade offs in the allocation of scarce public resources.
Bibliography: p. 342-365